Processo de seleção de sistemas integrados: possibilidades de modelagem com base na análise de decisões - Barreto, Allan de Azevedo (2003)
This work deals with ERP (Enterprise Resource Planning) systems selection, surveying the process specifically from the Decision Analysis standpoint. It aims to analyze the association between the satisfaction not only with the selected ERP alternative but also with the way the whole decision process was framed and managed, counting on variables specifically chosen for this matter. These variables are related, among others, to groups of decision criteria, and specific features of the selection process, regarding, the latter ones, to issues such as the treatment assigned to the risk inherent to the decision, and its possible understanding as a typical group decision situation. It questions the possibility of modeling the entire ERP selection process, based upon the Utility Theory’s normative proposal, and of the supposed existence of a gap between this proposal and the actual decision practices deployed in carrying that process through. It proposes a general mental model that aims to explain the way decision-makers approach the problem of ERP systems selection. It presents and proposes a dynamic model which would justify the existence of the aforementioned gap from the inability of the general mental model in apprehending all the complexity inherent to the problem of ERP systems selection.